Dipstick Assay for Rapid Detection of Beer Spoilage Organisms. (23rd November 2019) - Janagama, Harish K; Mai, Tam; Han, Sukkhyun; Nadala, Lourdes M; Nadala, Cesar; Samadpour, Mansour
Abstract: Background: Beer spoilage caused by wild yeast and bacteria is a major concern to both commercial and home brewers. Objective: To address this problem, Molecular Epidemiology Inc. (MEI, Seattle, WA) has developed a beer spoilage organism detection kit consisting of an enrichment media (BSE) and a multiplex PCR DNA dipstick that simultaneously detects these organisms within 2 h following enrichment. Methods: The kit was tested by using samples obtained from breweries located in the Greater Seattle area. Samples were spiked with the target microbes, when necessary, and used for assessing the performance characteristics of the DNA dipstick assay. Microbial enumerations were performed as per the standard microbiological plating methods. The suitability of the BSE medium to support the growth of beer spoilage microbes was compared with the industry-approved NBB-C medium (Dohler, Darmstadt, Germany). Results: Inclusivity (a panel of 50 isolates) and Exclusivity (a panel of 92 isolates) testing indicated that the dipstick assay can exclusively detect the indicated target beer spoilage microbes. When compared with the NBB-C medium (Dohler, Darmstadt, Germany) approved by the European Brewers Convention for beer spoilage organisms, the BSE medium supported faster growth of critical spoilage lactic acid bacteria such as Lactobacillus brevis, L. lindneri, and Pediococcus damnosus. Conclusions: The beer spoilage organism detection kit has a detection limit of 10 cells/mL. Highlights: The kit can be used at different stages of the brewing process, thus offering a convenient, cost effective, and faster test system for brewers interested in monitoring the quality of their product.